A concept for context-aware computing in manufacturing: the white goods case. Issue 8 (2nd August 2016) - Alexopoulos, Kosmas; Makris, Sotiris; Xanthakis, Vangelis; Sipsas, Konstantinos; Chryssolouris, George
Abstract : A key characteristic for industrial production in the Industry 4.0 paradigm is the connection of physical items like sensors, devices and enterprise assets, connected both to each other and to the Internet. In this Internet of Things environment, things will sense more data, become context-aware and provide added-value information to assist people take more relevant and valuable decisions. Context-aware information distribution may offer substantial value to manufacturing. It provides task-relevant information or services to users in a manufacturing shop-floor improving decision making through context-driven recommendations. This paper presents a context-aware information distribution system to support users in an industrial environment. The system aims at utilising data collected from sensors located at a shop-floor in order to increase the visibility of shop-floor processes by providing the right information, to the right people, at the right time. The system's architecture and key elements have been developed for a pilot implementation in the white goods industry and are presented in this study.